Use of didactic texts in basic education chemistry teaching (Research, Society and Development, 2020)
The present work presents notes about the role of reading in the Teaching of Chemistry and Natural Sciences. The study reports the development, application and analysis of reading mediations carried out during the internship as research by the Federal University of Pampa (UNIPAMPA) with a class of second year of high school in a state public school in the municipality of Caçapava do Sul, RS, during the Pedagogical Residency Program. In this context, reading and interpretation activities were developed related to texts present in textbooks that address the contents of Chemical Kinetics, Chemical Equilibrium and Electrochemistry. The research was of a qualitative nature and was organized by reading texts in textbooks. The analysis was carried out by the students' interaction with the presented texts and later elaboration of questions which they would like to be discussed and debated in the classroom. Questions were also presented whose answers were present in the texts in order to verify the students' ability to interpret. Data analysis was guided by the assumptions of Bardin's content analysis. From the observations of the reading activities and the observations made during the classes, categories of analysis emerged, namely: (i) learning difficulties in the teaching of Chemistry (ii), potential of reading activities in Chemistry classes; (iii) contributions to initial training. The results were satisfactory with regard to improvements in terms of understanding the chemical concepts presented. Thus, it can be seen that reading activities in Chemistry classes can contribute to learning, both by arousing interest in reading, and by improving the understanding of specific contents in the area of Natural Sciences.